Masa Keemasan Pendidikan Islam: (Studi Tentang Peran Khalifah Harun Al - Rasyid Dalam Pendidikan Islam) - journal, journal; Mustofa, Ali (STIT Muhammadiyah Paciran Lamongan, 2015)
Abstract: The role of the Caliph Harun al - Rasyid in Isl amic education is very large, including creating a varied curriculum that not only focuses on the problems of religion that are adapted to the level of education, establishing Khizanah al - Hikmah as an institution of translation, observation and reading roo m, building educational institutions , guaranteeing the lives of high - paying educators, utilizing the country's wealth to build educational infrastructure facilities, cooperating with developed countries to exchange information about science, developing le arning systems by developing Islamic education goals. Scientific treasures really grew rapidly in Baghdad under the rule of Caliph Harun al - Rashid. The era of Caliphate Harun al - Rasyid was a golden age in various fields, ranging from the fields of governme nt, socio - economic, administration, and the most prominent of science. Keywords: Abstrak: Peran Khalifah Harun al - Rasyid dalam pendidikan Islam sa ngat besar, diantaranya membuat kurikulum variatif yang tidak hanya fokus pada masalah keagmaan yang disesuaikan dengan jenjang pendidikan, mendirikan Khizanah al - Hikmah sebagai lembaga penerjemahan, observasi dan ruang baca, membangun lembaga - lembaga pend idikan, menjamin hidup para pendidik dengan gaji tinggi, memanfaatkan kekayaan negara untuk membangun sarana prasarana pendidikan, bekerjasama dengan negara maju untuk bertukar informasi tentang keilmuan, mengembangkan sistem pembelajaran dengan mengembang kan tujuan pendidikan Islam. Khazanah keilmuan benar - benar tumbuh pesat di Baghdad dibawah pemerintahan khalifah Harun al - Rasyid. Era kekhalifahan Harun al - Rasyid merupakan masa keemasan dalam berbagai bidang, mulai dari bidang pemerintahan, sosial - ekonomi , administrasi, dan yang paling menonjol ilmu pengetahuan.